Analysis of system reliability grinding in a concentrator, based on the criticality - Berger Vidal, Esther (2014)
The aim of this study is to present the process of grinding the ore concentrator plant a mining company, describing the settings of your threads and performing the calculation of the milling system reliability based on the criticality. Also, the main indicators are calculated for each team maintenance grinding area. The results enable companies maintenance decisions applying the constant monitoring of its milling equipment, which are of daily use of operators, establishing the criticality of any team in general regarding the occurrence of failure.